Fairy cat. 1 - Takano, Hisa (Seven Seas, 2025)
"A minuscule cat appears one rainy day, perched on Kanade's chair. But the moment he spots the tiny ball of fluff, it vanishes! Kanade knows fairy cats are a rare sight to behold, hiding out of reach in nooks and crannies--but now that he's seen one, he is determined to win its affection. Can Kanade coax the fairy cat out and befriend it?"